Training profile and performance in elite bodyboarders - Bruno, S.; Gonçalo, C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
Surfing can be considered an intermittent activity with different intensities, were fitness level of surfing athletes contributes to a better performance in both training and competition. Despite some knowledge about the fitness levels of elite surfers, there is limited published research examining the training profile of elite Bodyboarders and is influence in competition outcomes. During the Viana World Bodyboard Pro in Viana do Castelo, 49 elite bodyboarders, replied a retrospective questionnaire that include training habits. Spearmen correlation and Mann-Whitney test was applied to determine possible associations and comparation between groups. The ending ranking in the world tour is influenced by the practice of Physical Training and the fact that have a coach (p< 0.05). Bodyboarding is more than a recreational sport needing a new insight regarding sports specific season plan, that allow athletes compete at higher level. Specially for Junior athlete’s, physical training is key factor for accomplish better performance.